Effect of Comprehensive Nursing Interventions on Quality of life among Women with Stress Urinary Incontinence - Thabet, Asmaa Hamdy Mohammed; Mohammad, Zienab Abd-El-lateef; Abdalla, Medhat Ahmed; Abdelall, Hanan Abd-elrazik (International Journal of Membrane Science and Technology, 2023)
Stress Urinary Incontinence (SUI) is called a silent epidemic which is not a life threatening condition, but a worldwide problem at the same time which contributes to poor quality of life. Aim: Design, implement comprehensive nursing interventions for adult women with stress urinary incontinence and evaluate the effect of these interventions on improving their quality of life. Quazi experimental research design was utilized to conduct this study. This study was carried out in the Urology and Nephrology Assuit University Hospital and its affiliate Clinic. A sample of 50 adult women, the mean age of studied patients was (42.22±11.84). Two tools were used by the researcher namely: Tool I: A structured interview questionnaire sheet it included two parts, part i: demographic data of patient and part ii: medical& urological data assessment. Tool II: Kings Health Questionnaire (KHQ), it is a standardized questionnaire used to assess the impact of stress urinary incontinence on quality of life. The results showed that the quality of life among adult women with stress urinary incontinence were improved after the implementation of comprehensive nursing interventions with a statistically significance difference (p>0.05) in all quality of life domains. . We conclude that provided comprehensive nursing interventions are effective in improving QOL in adult women with SUI. Given the study results, it is recommended that expand of public education efforts through various methods about importance of health educational interventions for appropriate management of stress urinary incontinence among women.